2019
DOI: 10.1016/j.jsha.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of dabigatran dosing in patients with nonvalvular atrial fibrillation (NVAF): A retrospective study conducted in a tertiary care university hospital in the eastern province of Saudi Arabia

Abstract: BackgroundEstablishment of thromboembolism prevention remains a challenge despite the widespread consensus that thromboprophylaxis safely reduces patient morbidity and mortality. Dabigatran is a nonvitamin K antagonist oral anticoagulant (NOAC) which reduces the risk of thromboembolism. Proper dosing is important to achieve the maximum prophylactic benefit with a maintained safety profile.ObjectiveTo evaluate the appropriateness of dabigatran dosing for stroke and systemic embolism prevention in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…Some studies have even demonstrated that a proportion as high as 30% of patients were receiving a dose of dabigatran inappropriately low, after taking into account creatinine clearance, age, and bleeding risk …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have even demonstrated that a proportion as high as 30% of patients were receiving a dose of dabigatran inappropriately low, after taking into account creatinine clearance, age, and bleeding risk …”
Section: Resultsmentioning
confidence: 99%
“…34 Some studies have even demonstrated that a proportion as high as 30% of patients were receiving a dose of dabigatran inappropriately low, after taking into account creatinine clearance, age, and bleeding risk. 86 The predictors for dose reduction, other than dabigatran treatment, include advanced age, high CHA 2 DS 2 -VASc score, and high HAS-BLED score. 87 The role of the hospital pharmacist in medicines optimization goes obviously beyond OAC and studies undertaken in Brazil have shown that even in venous thromboembolism prevention, there is wide room for improvement as around 40% of hospitalized patients were found to receive inappropriate treatment.…”
Section: Secondary Care For Episodes Of Ill Healthmentioning
confidence: 99%
“…The fear for bleeding complications is a likely cause for this finding. Other studies also reported inappropriate prescription of DOAC in Saudi Arabia, including under-dosing or non-approved indications [ 13 , 15 , 22 , 23 ]. This finding points to the importance of ensuring an approval-conform intake of OAC medication in general.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin and DOAC are nationally approved in Saudi Arabia. Patient information leaflets were evaluated for the recommended intake regimen of all five anticoagulants (warfarin: QD only, dabigatran: BID only, apixaban: BID only, rivaroxaban: QD only, and edoxaban: QD only) [13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…When compared to warfarin, NOACs have significantly fewer drug–drug and food–drug interactions. NOACs also have the advantage of fixed dosing criteria, predictable pharmacokinetics and dynamic profile, less bleeding risk, and no need for monitoring [ 1 , 3 , 4 ]. However, NOACs have dose adjustments in renal-impaired patients since the kidney entirely clears them.…”
Section: Introductionmentioning
confidence: 99%